Brood Parasites in Zoology - Wills, Shonda, author 648201 (Delhi, India : White Word Publications, 2012)
Brood parasites are organisms that use the strategy of brood parasitism, a kind of kleptoparasitism found among birds, fish or insects, involving the manipulation and use of host individuals either of the same (intraspecific brood-parasitism) or different species (interspecific brood-parasitism) to raise the young of the brood-parasite. This relieves the parasitic parent from the investment of rearing young or building nests, enabling them to spend more time foraging, producing offspring etc. Additionally, the risk of egg loss to raiders such as raccoons is mitigated, by having distributed the eggs among a number of different nests. As this behavior is damaging to the host, it will often result in an evolutionary arms race between parasite and host.